Detailed analysis of immunologic effects of the cytotoxic T lymphocyte-associated antigen 4-blocking monoclonal antibody tremelimumab in peripheral blood of patients with melanoma. - Comin-Anduix, Begoña; Lee, Yohan; Jalil, Jason; Algazi, Alain; de la Rocha, Pilar; Camacho, Luis H; Bozon, Viviana A; Bulanhagui, Cecile A; Seja, Elisabeth; Villanueva, Arturo; Straatsma, Bradley R; Gualberto, Antonio; et al. (Journal of translational medicine, 2008)
CTLA4-blocking antibodies induce tumor regression in a subset of patients with melanoma. Analysis of immune parameters in peripheral blood may help define how responses are mediated.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Monoclonal; Antigens, CD; Cluster Analysis; CTLA-4 Antigen; Female; HLA-A Antigens; HLA-A2 Antigen; Humans; Immune System; Male; Melanoma; Middle Aged; T-Lymphocytes